A Full Textile Capacitive Woven Sensor. Issue 1 (3rd October 2022) - Martínez‐Estrada, Marc; Ventura, Heura; Gil, Ignacio; Fernández‐García, Raúl
Abstract: In this paper, a full textile capacitive woven sensor integrated over a textile substrate is presented. The sensor consists in an interdigitated capacitance prepared to measure moisture and/or presence detection. In order to evaluate the sensor response to moisture, capacitance has been measured by means of an LCR meter from 20 Hz to 20 kHz in a climatic chamber with a swept of the relative humidity (RH) from 30% to 90% at 20 °C. Subsequently, presence response is evaluated measuring the capacitance of the woven sensor meanwhile a person is sitting down and getting up. The woven sensor results demonstrate its functionality over moisture measurement where sensor capacitance changes from a minimum of 9.74 pF at 30% RH to a maximum of 2.31 uF at 90% RH. The presence detection is also demonstrated, which makes the capacitance variation change from a 10% of capacitance variation when the chair is empty, to a capacitance variation of 170% when a person is sitting on it. The adaptation of the weaving process to accomplish a fully integrated sensor provides a better repeatability than previous embroidered sensors and opens a door to being commercially produced. Abstract : In this paper, a full textile capacitive woven sensor integrated over a textile substrate is presented. The sensor consists in an interdigitated capacitance prepared to measure moisture and/or presence detection. Woven process adaptation of these sensor opens a door to a large‐scale textile sensor production.